Unveiling the dynamic relationship of viruses and/or symbiotic bacteria with plant resilience in abiotic stress - Vasudha Sharma; Shakeel A. Mohammed; Nisha Devi; Gourav Vats; Hardeep S. Tuli; Adesh K. Saini; Yashika W. Dhir; Sunny Dhir; Bharat Singh (Stress Biology, 2024)
Abstract In the ecosphere, plants interact with environmental biotic and abiotic partners, where unbalanced interactions can induce unfavourable stress conditions. Abiotic factors (temperature, water, and salt) are primarily required for plants healthy survival, and any change in their availability is reflected as a stress signal. In certain cases, the presence of infectious pathogens such as viruses, bacteria, fungi, protozoa, nematodes, and insects can also create stress conditions in plants, leading to the emergence of disease or deficiency symptoms. While these symptoms are often typical of abiotic or biotic stress, however, there are instances where they can intensify under specific conditions. Here, we primarily summarize the viral interactions with plants during abiotic stress to understand how these associations are linked together during viral pathogenesis. Secondly, focus is given to the beneficial effects of root-associated symbiotic bacteria in fulfilling the basic needs of plants during normal as well as abiotic stress conditions. The modulations of plant functional proteins, and their occurrence/cross-talk, with pathogen (virus) and symbiont (bacteria) molecules are also discussed. Furthermore, we have highlighted the biochemical and systematic adaptations that develop in plants due to bacterial symbiosis to encounter stress hallmarks. Lastly, directions are provided towards exploring potential rhizospheric bacteria to maintain plant-microbes ecosystem and manage abiotic stress in plants to achieve better trait health in the horticulture crops.